Significance of serum complement levels in patients with gastrointestinal disease. - Ross, I N (1979)
Levels of the serum complement components, C3 and C4, in patients with Crohn's disease, ulcerative colitis, and miscellaneous gastrointestinal disorders were compared with those of normal blood donors. Significant increases of both components were found in all three patient groups, the highest being in patients with Crohn's disease. Generally, levels of C3 and C4 were lower in patients with inactive rather than active Crohn's disease and ulcerative colitis. These results provide some evidence in support of an immunological basis for inflammatory bowel disease. However, in view of the frequent elevation of C3 and C4 in other gastrointestinal diseases, it is equally possible that the complement components are behaving as acute phase proteins.